Level of Family Depression as Caregivers of Patients in the Intensive Care Room - Nugroho Ari Wibowo; Dian Puji Wahyuningsih; Diah Priyantini; Aries Chandra Ananditha (Indonesian Academia Health Sciences Journal, 2024)
Intensive Care Unit (ICU) is a hospital inpatient room for observation, care and therapy of patients who need treatment and who are life threatening and have complex needs, supported by special equipment. When a patient is in the ICU, the risk of death is higher, giving rise to problems with feelings of physical, psychological, social and spiritual stress. The aim of this study was to identify the level of depression in the families of patients undergoing treatment in the Intensive Care Room at Haji Hospital, East Java province. The research used a quantitative design with a descriptive approach to the families of patients treated in the Intensive Care ward of the Haji Hospital, East Java Province. A total of 85 respondents were recruited using purposive sampling. The research instrument used to identify the level of family depression experienced by respondents was the Beck Depression Inventory II (BDI II) questionnaire sheet. The results of the study showed that the level of depression in the families of patients in the Intensive Care room was 37 respondents (43.53%) experienced mild depression, 31 respondents (36.4%) experienced minimal depression, 11 respondents (12.94%) experienced moderate depression and 6 respondents (7.06%) experienced severe depression. Health workers provide comprehensive health services by helping patients and their families meet their biological, psychological and social needs, as well as providing support to always improve their spirituality by praying to God and always thinking positively in all events they experience in the hope of preventing depression during the treatment period. patient.